Linkages of QMS and soft EMS: perceptions of operations managers as modelled by SEM - Khalili, Amjad; Karim, A.N. Mustafizul; Ismail, Md Yusof; Che Daud, Mohd Radzi (Inderscience Enterprises Ltd., 2019)
Empirical studies in the contemporary operations management (OM) literature are found to be inadequate to explore whether the two ISO management standards namely, quality management system (QMS) and environmental management system (EMS) are integrated together in the same enterprise or not. This paper aims at investigating the linkages among QMS and soft EMS and establishing their associative relationships. In this context, a conceptual model is initially developed and subsequently examined in the Malaysian manufacturing industries in an empirical manner. The primary data, gathered from a sample of 329 Malaysian industries through a structured questionnaire, were analysed using techniques from both SPSS 22 and structural equation modelling (SEM). Both principal component analysis (PCA) and confirmatory factor analysis (CFA) were utilised. Findings show that the postulated hypothesis is both statistically and practically significant. Hence, the hypothesis is supported which reflects that both ISO standards (QMS and Soft EMS) can be integrated together in the same enterprise, and reiterates provisions for manufacturers to endure practicing these management standards to sustain their operations.